Climate Change and Marine-Coastal Resources - Gutiérrez, Alejandro (2008)
Climate change and its effects on the biosphere are now of World interest for both, scientists, some of them reluctant time ago to accept the relevancy of its effects, as for decision makers, mainly those from the privileged World now effectively interested on this argument that seems will drastically restrain our quality of life in the future. This essay is the result of a query on the climate change impact on the coastal marine resources in Costa Rica; therefore, in the following we have tried to answer such a question using the scientific information available.